The ordering of historical returns and the cross-section of subsequent returns - Mohrschladt, Hannes (Journal of Banking & Finance, 2021)
We show that the ordering of historical stock returns significantly predicts the cross-section of subsequent returns. More specifically, stocks with comparably high recent and low distant returns experience low subsequent returns and vice versa. Our new measure of chronological return ordering yields significant decile return spreads after accounting for a wide range of asset pricing factors. This finding holds for both a monthly and an annual formation period and is valid beyond micro-structure, reversal, and momentum effects. Further analyses on limits to arbitrage, investor attention, and informed option trading support a mispricing-based explanation for parts of the documented return predictability.